Suppression of interleukin 2 secretion and interleukin 2 receptor expression during tsetse-transmitted trypanosomiasis in cattle - Sileghem, M.R.; Flynn, J.N. (Wiley, 1992)
Infection with Trypanosoma congolense in cattle was found to be associated with a profound suppression of the host's immune system. Lymph node cells from infected cattle were unable to secrete interleukin 2 (IL 2) in vitro following mitogenic stimulation and the exogenous supply of IL 2 did not restore T cell proliferative responses. This was associated with an impaired expression of the α chain of the IL 2 receptor (IL 2R α). Co‐culture experiments, where cells from an infected animal were mixed with cells from a major histocompatibility complex‐matched normal animal, demonstrated the presence of suppressor cells capable of blocking both IL 2 secretion and IL 2Rα expression. Removal of macrophages by fluorescence‐activated cell sorting abrogated suppression in such co‐cultures. Following depletion of macrophages, lymph node cells from an infected animal expressed IL 2Rα at a normal level, but remained incapable of producing IL 2. Hence, the unresponsiveness was associated with macrophage‐like suppressor cells which operated at the level of both IL 2 secretion and IL 2Rα expression, and to an intrinsic unresponsiveness of the T cells which was restricted to IL 2 secretion.Inhibition of prostaglandin synthesis by addition of indomethacin failed to abrogate suppression of either IL 2 secretion or IL 2Rα expression. This revealed a major difference between the regulation of suppression in murine model infections where the suppression of IL 2 secretion is due to prostaglandin secretion, and the situation in cattle where prostaglandins would not appear to be involved.